Microsoft Excel 2019 : programming by example with VBA, XML, and ASP - Korol, Julitta (Mercury Learning and Information, 2019)
A practical, how-to book on Excel programming, suitable for readers already proficient with the Excel user interface (UI). If you are looking to automate Excel routine tasks, this book will progressively introduce you to programming concepts via numerous illustrated hands-on exercises. More advanced topics are demonstrated via custom projects. From recording and editing a macro and writing VBA code to working with XML documents and using Classic ASP pages to access and display data on the Web, this book takes you on a programming journey that will change the way you work with Excel. The book provides information on performing automatic operations on files, folders, and other Microsoft Office applications. It also covers proper use of event procedures, testing and debugging, and guides you through programming advanced Excel features such as PivotTables, PivotCharts, and the Ribbon interface. --